In Silico Study for Similar FDA Approved Drugs as Inhibitors of SARS-CoV-2 Spike and the Host Receptor Proteins - Israa Mohamed Shamkh; Dina Pratiwi; Hanaa S. Omar; Nour El-Houda A. Reyad (Journal of Molecular Docking, 2021)
The severe acute respiratory syndrome coronavirus 2, known as COVID-19, has been hideously increased worldwide. The disease began in Wuhan, China, around December 2019, then spread to most countries. Social distancing is the best procedure to prevent infection. Screening the available database containing millions of drug molecules or phytochemicals has become rapid and straightforward because of the computer-aided drug design (CADD) methods. In the present study, 300 phytochemicals and cellulose ether derivatives are screened through a docking study. Docking analysis showed that only four molecules (a-neohesperidin, quercetin 3-O-glucosylrutinoside, 14-ketostypodiol diacetate, and hydroxypropyl methylcellulose) were able to interact with the spike protein. However, two among them (quercetin 3-O-glucosylrutinoside and 14-ketostypodiol diacetate) could interact with the host cell receptor (ACE2) of SARS-CoV-2. The binding affinity of the four compounds is high. Still, according to Lipinski's rule of five, only 14-ketostypodiol diacetate was selected as a drug molecule due to its pharmacokinetic and ADMET properties. Screening for drug analogs to the 14-ketostypodiol diacetate detected five approved drugs. Docking analysis of these drugs with the target proteins showed that the five drugs interact with the host receptor protein, and three interact with viral spike protein. Accordingly, we suggest that molecular docking and drug analogs studies could support rapid drug development. In addition, future perspectives on therapeutic applications of 14-ketostypodiol diacetate are required for using it against SARS-CoV-2 infections.